A Challenging Case of Subcutaneous and Mucosal Haemorrhage Caused by Urticarial Vasculitis (Urticaria Haemorrhagica Profunda) - Anne Birgitte Simonsen; Mikkel Hjordt Larsen; Christian von Buchwald; Kristian Kofoed (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)